Low consumption of fruits and vegetables among adults in Uganda: findings from a countrywide cross-sectional survey - Steven Ndugwa Kabwama; Silver K. Bahendeka; Ronald Wesonga; Gerald Mutungi; David Guwatudde (BMC, 2019)
Abstract Introduction Adequate consumption of fruits and vegetables has protective benefits against development of coronary heart disease, hypertension and chronic obstructive pulmonary disease. However, approximately 2.7 million deaths annually can be attributed to inadequate fruit and vegetable consumption. We analyzed data from a countrywide survey in Uganda, to estimate the prevalence of adequate fruit and/ or vegetable consumption, and identify associated factors. Methods Data were collected using the World Health Organization STEPwise approach to surveillance, a standard approach to surveillance of risk factors for Non Communicable Diseases. Fruit and vegetable consumption was assessed by asking participants the number of days in a typical week they eat fruits or vegetables and the number of servings eaten in one of those days. Adequate fruit and/ or vegetable consumption was defined as consuming 5 or more servings of fruits and/ or vegetables per day in a typical week. We used modified Poisson regression analysis to estimate prevalence risk ratios (PRRs) and identify factors associated with eating 5 or more servings of fruits and/ or vegetables per day, per week. Results Of 3962 participants, 484 (12.2%) consumed 5 or more servings of fruits and/ or vegetables per day in a typical week. Participants who were married or cohabiting were more likely to consume at least 5 servings of fruits and/ or vegetables per day in a typical week compared with those who had never been married PRR = 1.51 [95% CI 1.07-2.14]. Compared with participants from Western region, those from Central region were more likely to consume 5 or more servings of fruits and/ or vegetables per day in a typical week, PRR = 3.54 [95% CI 2.46-5.10] as were those from Northern, PRR = 2.90 [95% CI 2.00-4.23] and Eastern regions PRR = 1.60 [95% CI 1.04-2.47]. Conclusions Fruit and vegetable consumption in Uganda is low and does not differ significantly across social and demographic characteristics, except marital status and geographical region of residence. There is a need to develop and strengthen policies that promote adequate consumption of fruits and vegetables in the Ugandan population.